The promoter and transcriptional unit of a novel herpes simplex virus 1 alpha gene are contained in, and encode a protein in frame with, the open reading frame of the alpha 22 gene. - Carter, K L (1996)
The herpes simplex virus type 1 genome encodes a set of genes (alpha genes) expressed in the absence of de novo viral protein synthesis. Earlier studies have shown that the product of the alpha 22 gene, a member of this set, is nucleotidylylated by casein kinase II and phosphorylated by viral protein kinases encoded by UL13 and US3. Mutants lacking the carboxyl-terminal domain starting with amino acid 200 exhibit reduced capacity to replicate in primary human cell strains or in cells of rodent derivation and also exhibit reduced expression of a subset of gamma or late genes. We report that the domain of the alpha 22 gene is transcribed by two 3'-coterminal mRNAs. The longer transcript reported encodes the 420-amino-acid alpha 22 protein, whereas the shorter transcript reported here encodes a protein containing the carboxyl-terminal 273 amino acids of the alpha 22 protein. The shorter gene is designated US1.5. The US1.5 mRNA is synthesized in cells infected and maintained in the presence of cycloheximide and under other conditions which restrict viral gene expression to alpha genes. In-frame insertion of linkers encoding 18, 21, or 22 amino acids after codon 200 or 240 of the alpha 22 protein did not affect the known functions or phenotype associated with the wild-type alpha 22 gene or its product. Earlier studies have placed the nucleotidylylated sequences in the amino-terminal portion of the protein. The results of these studies indicate that the US1.5 gene encodes the functions associated with replication in human primary or rodent cells and optimal expression of alpha 0 and gamma genes. This finding brings the number of genes known to map in the unique short region of the herpes simplex virus type 1 DNA to 14 and the total number of different genes to 78.